Fatal Acanthamoeba Encephalitis in a Patient With a Total Artificial Heart (Syncardia) Device. (19th August 2014) - Tan, Susanna K.; Gajurel, Kiran; Tung, Christie; Albers, Gregory; Deresinski, Stan; Montoya, Jose G.; Sheikh, Ahmad Y.; Banerjee, Dipanjan; Ha, Richard
Abstract: Acanthamoeba encephalitis is an uncommon but often fatal infection complication. Here we report the first case of Acanthamoeba encephalitis in a patient with a Total Artificial Heart device.